ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI PEMERINTAH NOMOR 01. PADA LAPORAN KEUANGAN KPU KOTA BOGOR. - Muhammad Rian Syauri; Andy Lasmana; Indra Cahya Kusuma (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2026)
The study concludes that the level of conformity of the Bogor City General Elections Commission (KPU) financial statements for the 2020–2024 period with PSAP No. 01 reached 60%, while the level of non-conformity was 40%. The financial statement components that complied with PSAP No. 01 include the Operational Report (LO), Statement of Changes in Equity (LPE), and Notes to the Financial Statements (CaLK). However, non-conformities were still identified in the Budget Realization Report (LRA) and Balance Sheet. Therefore, the presentation of the Bogor City KPU financial statements can be categorized as moderately compliant with PSAP No. 01. Nevertheless, improvements are still required in several components to enhance the level of compliance and strengthen the transparency and accountability of public financial management.